Pengetahuan Etnobotani, Keanekaragaman Tumbuhan Berguna, dan Kearifan Ekologis Lokal Masyarakat Adat Rongkong dalam Pengelolaan Perhutanan Sosial - Novi Herman Sada; Maria Maria; Wiwi Oktaviani; Witno Witno; Elon Raysabda; Andi Utami Batari Putri (MAKILA, 2026)
This study investigated the ethnobotanical knowledge of the indigenous Rongkong community in Rinding Allo Village, Rongkong District, North Luwu Regency, Indonesia, with particular emphasis on plant resource utilization and its relationship with local wisdom, cultural practices, and forest-based ecosystem services. Data were collected through field surveys, participatory observation, and semi-structured interviews with 59 respondents selected using the Slovin sampling formula. The findings revealed that the community utilizes 71 plant species belonging to 43 botanical families for various purposes, including food, traditional medicine, livestock feed, construction materials, fuelwood, handicrafts, and socio-cultural as well as religious ceremonies. Leaves were the most frequently utilized plant part, followed by roots, stems, rhizomes, fruits, and other plant organs. The diverse use of plant resources reflects the community’s long-standing ecological knowledge and contributes to household subsistence, local livelihoods, cultural identity preservation, and the sustainability of forest ecosystem functions. Traditional ethnobotanical knowledge is transmitted across generations through customary practices and oral traditions; however, it is increasingly threatened by socio-cultural transformation and modernization. Therefore, systematic documentation, revitalization of local knowledge systems, and community-based conservation strategies are essential to safeguard traditional ethnobotanical heritage while supporting biodiversity conservation and sustainable forest management. This study highlights the important role of indigenous knowledge in strengthening community–forest relationships within a sustainable development framework.